Financial Feasibility of Sugar and Alcohol Agroindustries: Kelayakan Finansial Agroindustri Gula dan Alkohol - Rahmat Saleh; Nurafifah Wulandari (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2026)
This study evaluates the financial feasibility of an agro-industrial project by PT XYZ, which processes sugar and alcohol, using key investment appraisal metrics. A quantitative financial analysis was conducted employing Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI). Results indicate a positive NPV, confirming the project’s potential for profit, and a high PI, reflecting efficient capital use. The investment is recoverable within 2 years and 5 months, demonstrating a short payback period. However, the relatively low IRR highlights financial risks linked to raw material price fluctuations and market uncertainty. These findings provide critical insights for agro-industrial investors and managers, emphasizing the need for robust risk mitigation strategies alongside strong financial indicators when making investment decisions.